Hak atas Lingkungan Hidup yang Baik dan Sehat sebagai Hak Asasi Manusia: Tantangan Konstitusional dan Implementasinya di Indonesia - Ulfi Dwiani; Windi Putri Oktapiani; Siti Ulfah Awaliyah; Jasmine Az-Zahra; Yoyoh (Journal of Legal, Political, and Humanistic Inquiry, 2025)
The right to a good and healthy environment has been universally recognized as an integral part of human rights (HAM), as affirmed in the Stockholm Declaration 1972, Rio Declaration 1992, and Article 28H paragraph (1) of the 1945 Constitution of Indonesia. This study analyzes the constitutional recognition of this right in Indonesia, the challenges in its implementation amid environmental degradation due to industrialization and urbanization, and its legal implications for human rights enforcement. Employing a normative juridical approach with analysis of international and national legal documents and a case study on the Citarum River pollution, the findings indicate that while normatively robust, this right remains weak in enforcement due to ineffective sanctions and poor inter-agency coordination. Reforms in human rights-based legislation and strengthening of environmental courts are recommended to realize a healthy environment as a substantive human right.